2015
DOI: 10.1017/s0001924000010484
|View full text |Cite
|
Sign up to set email alerts
|

Flight in nature II: How animal flyers land

Abstract: In this review paper, different landing strategies of diverse species of animal flyers and gliders, both extinct and extant, are analysed. These methods vary depending on the animal group and the sensory system used by the animal to detect its landing site. In almost all species the use of delayed stall during the landing manoeuvre was observed. Sometimes wing flapping was used to aid in deceleration. With respect to guidance and navigation, most insect, bird and mammal gliders use their vision to guide them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The biomechanics of the takeoff before flight and jump have been well studied across a variety 255 of different insect species (Manzanera and Smith, 2015). Various sophisticated mechanisms and structural adaptations have been shown to allow for example efficient energy storage, highly synchronized leg movement and detachment from the surface (Christian, 1978;Rothschild et al, 1972;Sutton and Burrows, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomechanics of the takeoff before flight and jump have been well studied across a variety 255 of different insect species (Manzanera and Smith, 2015). Various sophisticated mechanisms and structural adaptations have been shown to allow for example efficient energy storage, highly synchronized leg movement and detachment from the surface (Christian, 1978;Rothschild et al, 1972;Sutton and Burrows, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In general, flight and jumping movements can be subdivided into three major phases: take-off, aerial phase and landing. However, whilst landing after flight is mostly a predictable movement which is actively controlled by the insect (Borst, 1986;Manzanera and Smith, 2015), landing 30 after a jumping movement has additional challenges. Although the initial trajectory of the takeoff and even the orientation of the body might be controlled by several jumping insect species (Alexander, 1995;Faisal and Matheson, 2001;Heitler, 1974;Rothschild et al, 1972;Sutton andBurrows, 2008, 2011), external factors such as gusts of wind or unforeseen obstacles make it extremely difficult to reliably predict the mechanical properties of the landing site 35 (Bennet-Clark and Alder, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The study of natural systems revealed that evolutionary adaptation enables objects and processes in nature to be highly effective and robust (Bhushan, ; Kovač, ). While the natural world evolves, its processes provides an extensive source of inspiration for creating comprehensive models of artificial systems that can mimic certain functions of their counterparts in nature (Manzanera & Smith, ). The bioinspired design paradigm (Kovač, ) and perching principles (Liu, Ravi, Kolomenskiy, & Tanaka, ; Roderick, Cutkosky, & Lentink, ) provide cross‐disciplinary approaches to developing new devices by mimicking the natural world in the way of adopting concepts and principles in nature to solve engineering challenges.…”
Section: The Bioinspired Strategy and Mechanism For Autonomous Landingmentioning
confidence: 99%
“…Here we briefly review the functions of legs in selected examples of animal flyers, from insects, birds, and mammals, as illustrated in the ascending order of size in Figure . More detailed reviews of landing strategies in the animal kingdom can be found in literature (Altenbach, ; Carruthers, Taylor, Walker, & Thomas, ; Carruthers, Thomas, & Taylor, ; Evangelista, Kraft, Dacke, Reinhard & Srinivasan, ; Kovač, ; Manzanera & Smith, ).…”
Section: The Bioinspired Strategy and Mechanism For Autonomous Landingmentioning
confidence: 99%
See 1 more Smart Citation